Monitoring the Future: A Continuing Study of American Youth (12th-Grade Survey), 2013 - Johnston, Lloyd D. ([Verlag nicht ermittelbar], 2014)
This survey of 12th-grade students is part of a series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth. Students are randomly assigned to complete one of six questionnaires, each with a different subset of topical questions, but all containing a set of "core" questions on demographics and drug use. There are about 1,400 variables across the questionnaires. Drugs covered by this survey include tobacco, smokeless tobacco, alcohol, marijuana, hashish, prescription medications, over-the-counter medications, LSD, hallucinogens, amphetamines (stimulants), Ritalin (methylphenidate), Quaaludes (methaqualone), barbiturates (tranquilizers), cocaine, crack cocaine, GHB (gamma hydroxy butyrate), ecstasy, methamphetamine, and heroin. Other topics include attitudes toward religion, changing roles for women, educational aspirations, self-esteem, exposure to drug education, and violence and crime (both in and out of school).